2012
DOI: 10.1371/journal.pntd.0001770
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Silencing of Brugia malayi Trehalose-6-Phosphate Phosphatase Impairs Embryogenesis and In Vivo Development of Infective Larvae in Jirds

Abstract: BackgroundThe trehalose metabolic enzymes have been considered as potential targets for drug or vaccine in several organisms such as Mycobacterium, plant nematodes, insects and fungi due to crucial role of sugar trehalose in embryogenesis, glucose uptake and protection from stress. Trehalose-6-phosphate phosphatase (TPP) is one of the enzymes of trehalose biosynthesis that has not been reported in mammals. Silencing of tpp gene in Caenorhabditis elegans revealed an indispensable functional role of TPP in nemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…1,2 T6PP functions both in the synthesis of a,a 0 -trehalose, which is required for survival and/or virulence, and in the removal of T6PP that is necessary to avoid cell toxicity. [1][2][3][4][5] Because a,a 0 -trehalose synthesis is restricted to plants and in particular to lower organisms, including parasitic nematodes, opportunistic fungi and pathogenic bacteria, T6PP has been identified as an attractive platform for the development of small molecule inhibitors to serve as antihelminthics, antifungals and antibacterials. 2,6,7 To this end, large quantities of homogenous T6P are required to support high-throughput inhibitor screening, evaluation and SAR analyses.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 T6PP functions both in the synthesis of a,a 0 -trehalose, which is required for survival and/or virulence, and in the removal of T6PP that is necessary to avoid cell toxicity. [1][2][3][4][5] Because a,a 0 -trehalose synthesis is restricted to plants and in particular to lower organisms, including parasitic nematodes, opportunistic fungi and pathogenic bacteria, T6PP has been identified as an attractive platform for the development of small molecule inhibitors to serve as antihelminthics, antifungals and antibacterials. 2,6,7 To this end, large quantities of homogenous T6P are required to support high-throughput inhibitor screening, evaluation and SAR analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Kormish and McGhee (2005) developed the lethal gob-1 phenotype to demonstrate that T6P accumulation leads to nematode death. Kushwaha et al (2012) also demonstrated that tpp gene silencing was lethal for Brugia malayi larvae and that the observed lethal effects impaired in vivo development.…”
Section: Trehalose-6-phosphate Phosphatase (Tpp)mentioning
confidence: 86%
“…A recent screening of the PaDAW1 genome did not confirm the presence of these proteins, possibly explaining the limited efficiency of RNAi [10]. However, Kushwaha et al [37] reported that B . malayi genes can be efficiently silenced by RNAi despite the lack of SID-1 and SID-2 in this species, suggesting the involvement of other genes.…”
Section: Discussionmentioning
confidence: 99%